2013
DOI: 10.1093/eurpub/ckt010
|View full text |Cite
|
Sign up to set email alerts
|

Health sector costs of self-reported food allergy in Europe: a patient-based cost of illness study

Abstract: Food allergy is associated with higher health care costs. Severity of allergic symptoms is a key explanatory factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 16 publications
0
47
1
Order By: Relevance
“…Likewise, these households may also seek significantly more contact with health care professionals than households without a food allergic child. 6 Among adolescents, we did not find a significant difference in overall direct costs between cases and controls. We suggest that there are at least 4 explanations for this observation.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Likewise, these households may also seek significantly more contact with health care professionals than households without a food allergic child. 6 Among adolescents, we did not find a significant difference in overall direct costs between cases and controls. We suggest that there are at least 4 explanations for this observation.…”
Section: Discussioncontrasting
confidence: 56%
“…3 Others have shown that heightened parental anxiety regarding their child's food allergies 5 and poor health-related quality of life (HRQL) 5 may contribute to these higher costs in food allergic children. However, much research in this field has focused on children and adolescents as a single group, 3,4 or was restricted only to children, 6 despite suggestions that the two age groups will likely behave differently due to their developmental stages. 5 Previous reports on food allergy-associated costs are separated into direct and indirect costs, 1,3 and include socioeconomic costs and lost time and productivity, respectively.…”
Section: Abbreviations Usedmentioning
confidence: 99%
“…The annual total household costs were €3961 higher for children and €4792 higher for adolescents than for the controls . In addition, the higher annual healthcare costs were associated with food allergies in a European patient‐based, cost‐of‐illness study . Thus, the costs of the school lunches we evaluated in this study were only part of the total costs of food allergies to the families and to the community.…”
Section: Discussionmentioning
confidence: 90%
“…Yet, health-related quality of life does not appear to differ between the phenotypes [18]. Moreover, both phenotypes burden healthcare systems [19, 20], society [21] and households [21, 22]. …”
Section: Introductionmentioning
confidence: 99%